The Production Process of the Convection Business in Nagari Batu Taba, Ampek Angkek District, West Sumatra - Wihandira Wihandira; Weni Nelmira (Jurusan Pendidikan Kesejahteraan Keluarga, Fakultas Teknik, Universitas Negeri Semarang, 2023)
The convection industry in Batu Bata is a major contributor to the local community's income, as evidenced by the numerous businesses that have been passed down through generations and have experienced successful growth. However, as a home-based convection industry, some businesses have faced challenges such as a lack of product planning that caters to customer needs and fashion trends, inadequate management of the workforce, including a lack of a permanent workforce, poor regulation of employee working hours, and an unclear wage system. This study seeks to examine the production processes employed by entrepreneurs in Batu Taba, focusing specifically on production planning, production processes, and quality control. A quantitative descriptive method was used, utilizing data collected from surveys, interviews, and observations. The results indicated that 47% of respondents had effective production planning and 53% did not. 74% of respondents carried out the production process appropriately, while 25% did not. 78% of respondents carried out quality control effectively, and only 22% did not carry out the quality control process properly.